The magic arrow - Banal, Bolet; Banal, Korinne C. (Quezon City : Adarna House, 2021)
"The mighty king always says "NO"$1 (BNO to books with colorful pictures, NO to reading out loud, and NO to singing and laughing in the streets. What happens when island kingdom's blacksmith decides it's time for the king to change his mind?"--Back cover.s
Ages 8 and above.
Keywords: Dictators -- Juvenile fiction; Children's stories, Filipino